Improvement of the bandwidth and scattering parameter performances of 5G branch-line coupler design for the use in Intelligent Transportation System (ITS) - Zaidel, D.N.K.A. (Universiti Teknikal Malaysia Melaka, 2018)
This paper presents a design of 5G branch-line coupler that operates at 10 GHz frequency range. The proposed coupler is implemented with four stubs and two slots to improve the performances including the scattering parameter and also the bandwidth. Advanced Design System (ADS) software is used to design and perform the simulation stage. The proposed 5G coupler with stub and slot technique has enhances the bandwidth up to 60% as compared to the one proposed earlier in the literature. Additionally, the simulation results show that the scattering parameter and phase differences have also improved. The proposed design is suitable to be used later in Butler Matrix for Intelligent Transportation System (ITS) application.